1998
DOI: 10.1095/biolreprod59.6.1349
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinase Expression in Macaca mulatta Endometrium: Evidence for Zone-Specific Regulatory Tissue Gradients1

Abstract: Matrix metalloproteinases (MMPs) are highly expressed in the human endometrium during menstruation, and these enzymes participate in the cyclic destruction and regeneration characteristic of the primate endometrium. To examine hormonal regulation of MMPs in vivo, we evaluated MMP expression and localization in the endometrium of ovariectomized rhesus macaques under various hormonal conditions. Although all MMPs were up-regulated by progesterone (P4) withdrawal, their expression declined spontaneously after men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
77
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 34 publications
12
77
0
Order By: Relevance
“…This observation indicates a possible differential requirement of HOXA10-regulated transcriptome in the two compartments. Such zone-specific, differential expression of some genes has been observed in the primate endometrium (Rudolph-Owen et al 1998, Torres et al 2002, Slayden & Brenner 2004; these are thought to be involved in endowing specialized roles to the functionalis zone for implantation and also in the regulation of menstruation (Rudolph-Owen et al 1998, Torres et al 2002. Since the HOX family of genes is known to have a role in body segmentation by regulating the differential distribution of the morphogens (Pearson et al 2005), it is tempting to hypothesize that the zone-specific distribution of HOXA10 would lead to creation of precincts of microenvironments within the uterus in preparation for implantation.…”
Section: Discussionmentioning
confidence: 98%
“…This observation indicates a possible differential requirement of HOXA10-regulated transcriptome in the two compartments. Such zone-specific, differential expression of some genes has been observed in the primate endometrium (Rudolph-Owen et al 1998, Torres et al 2002, Slayden & Brenner 2004; these are thought to be involved in endowing specialized roles to the functionalis zone for implantation and also in the regulation of menstruation (Rudolph-Owen et al 1998, Torres et al 2002. Since the HOX family of genes is known to have a role in body segmentation by regulating the differential distribution of the morphogens (Pearson et al 2005), it is tempting to hypothesize that the zone-specific distribution of HOXA10 would lead to creation of precincts of microenvironments within the uterus in preparation for implantation.…”
Section: Discussionmentioning
confidence: 98%
“…MMP-1 mRNA is found at or around arterioles and small vessels and in stromal cells in the zona functionalis during the menstrual phase (Hulboy et al 1997). Segments of the spiral arteries running through the zona functionalis, but not the segments running through the zona basalis, show strong expression of metalloproteinases during the menstrual phase (Rudolph-Owen et al 1998).…”
Section: Noncellular Componentsmentioning
confidence: 99%
“…The pattern of expression of endometrial metalloproteinases during the menstrual cycle in macaques is similar to that reported for women. In both species, matrix metalloproteinases are strongly upregulated during the decline of progesterone levels in the late luteal phase, and their expression declines after menstruation (Rudolph-Owen et al 1998). Several metalloproteinases are highly expressed in areas where tissue breakdown occurs during the menstrual phase (Hulboy et al 1997).…”
Section: Noncellular Componentsmentioning
confidence: 99%
“…Adult rhesus macaques (Macaca mulatta) were ovariectomized and artificial cycles (Rudolph-Owen et al, 1998;Slayden et al, 2001a) were initiated in the animals by inserting a subcutaneous (s.c.) capsule that released E 2 to induce a 14 day proliferative phase, followed by insertion of a P capsule s.c. to induce a 14 day secretory phase. The levels of E 2 and P produced by these capsules were within the normal range for macaques during the natural cycle.…”
Section: Animal Treatmentsmentioning
confidence: 99%
“…We collected endometrium for analysis at the following phases: 1) the end of the proliferative phase, 2) the end of the secretory phase, and 3) during days 1-6 of the next cycle induced by P withdrawal. We refer to the transition between cycles as the luteal follicular transition (LFT) (Rudolph-Owen et al, 1998). We also evaluated the action of several PA compounds including mifepristone (Roussel UCLAF), ZK 137 316, and ZK 230 211 (Schering AG) administered chronically to artificially-cycled macaques (Hirst et al, 1992;Slayden et al, 1993Slayden et al, , 2001aSlayden and Brenner, 2003).…”
Section: Animal Treatmentsmentioning
confidence: 99%